Analysis of the Influence of Leadership Style and Motivation on the Level of Employee Productivity at PT. Sumber Setamurni - Selvi Angeline; Hernawaty Manalu (Jurnal Mantik, 2022)
This study aims to determine the effect of leadership style and motivation on the level of employee productivity at PT. Sumber Setamurni. The type of research used in this research is associative quantitative method. The sample in this study was 50 employees. In this study, the questionnaire will be distributed as measured by a Likert scale. The analytical method used is multiple linear regression analysis, ttest (partial testing), F test (simultaneous testing). From the results of the study that leadership style has a positive and significant effect on employee productivity. Meanwhile, motivation has a positive and significant effect on employee productivity. Meanwhile, leadership style and motivation affect employee productivity. This makes leadership style the most dominant variable affecting employee productivity at PT. Sumber Setamurni.